2013
DOI: 10.1161/strokeaha.111.000402
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Apixaban, Dabigatran, Rivaroxaban, and Warfarin for Stroke Prevention in Atrial Fibrillation

Abstract: Background and Purpose-To estimate the cost-effectiveness of stroke prevention in patients with nonvalvular atrial fibrilla tion by using novel oral anticoagulants apixaban 5 mg, dabigatran 150 mg, and rivaroxaban 20 mg compared with warfarin. Methods-A Markov decision-analysis model was constructed using data from clinical trials to evaluate lifetime costs and quality-adjusted life-years of novel oral anticoagulants compared with warfarin. The modeled population was a hypothetical cohort of 70-year-old patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
167
2
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(185 citation statements)
references
References 39 publications
7
167
2
6
Order By: Relevance
“…Their CEACs compared only rivaroxaban with warfarin but found close to a 60% probability that rivaroxaban was cost-effective in the £20,000-30,000 threshold range, similar to our probability that a NOAC (apixaban) was most cost-effective. The Harrington et al 38 model in the US setting compared apixaban (5 mg bd), dabigatran (110 mg bd), rivaroxaban (20 mg od), and warfarin, and found that apixaban had the highest expected QALYs, followed by dabigatran, rivaroxaban and warfarin. Our model also found apixaban to have the highest expected QALYs and that dabigatran and rivaroxaban would have higher expected QALYs than warfarin, although the high degree of uncertainty in our results renders them compatible with the order found by Harrington et al 38 Harrington et al 38 also found apixaban and dabigatran to be cost-effective compared with warfarin, and other US studies found apixaban, 36 rivaroxaban 37 and dabigatran 34 to be cost-effective compared with warfarin.…”
Section: Cost-effectiveness Results (1) Stroke Prevention In Atrial Fmentioning
confidence: 99%
“…Their CEACs compared only rivaroxaban with warfarin but found close to a 60% probability that rivaroxaban was cost-effective in the £20,000-30,000 threshold range, similar to our probability that a NOAC (apixaban) was most cost-effective. The Harrington et al 38 model in the US setting compared apixaban (5 mg bd), dabigatran (110 mg bd), rivaroxaban (20 mg od), and warfarin, and found that apixaban had the highest expected QALYs, followed by dabigatran, rivaroxaban and warfarin. Our model also found apixaban to have the highest expected QALYs and that dabigatran and rivaroxaban would have higher expected QALYs than warfarin, although the high degree of uncertainty in our results renders them compatible with the order found by Harrington et al 38 Harrington et al 38 also found apixaban and dabigatran to be cost-effective compared with warfarin, and other US studies found apixaban, 36 rivaroxaban 37 and dabigatran 34 to be cost-effective compared with warfarin.…”
Section: Cost-effectiveness Results (1) Stroke Prevention In Atrial Fmentioning
confidence: 99%
“…Nonetheless, these patients are rigorously selected for dabigatran treatment, are well characterised clinically, and have been followed for treatment complications for six months after cardioversion. Furthermore, although the cost of dabigatran is higher than of warfarin, recent analyses have indicated that dabigatran 150 mg is a cost-effective alternative to warfarin for elderly patients with high risk for stroke [18,19]. Whether this is the case for lower risk patients, such as those included in the present study and in different health care systems, is not known [20].…”
Section: Discussionmentioning
confidence: 82%
“…El momento de reintroducir la anticoagulación no está bien definido; en algunos estudios se propone reintroducir cuando haya estabilidad hemodinámica 18 y en otros a partir del cuarto día tras el diagnóstico 19 . Hay que resaltar que el 57% de nuestros pacientes en tratamiento con acenocumarol presentaban INR en rango supraterapéutico, por lo que se debe insistir en la recomendación de controlar de forma estrecha las dosis de acenocumarol para evitar complicaciones hemorrágicas y, en pacientes con INR lábil o elevado riesgo de sangrado, plantear otras alternativas terapéuticas como los anticoagulantes de acción directa 12,[20][21][22][23][24][25][26] . La insuficiencia renal es un factor de riesgo de complicaciones hemorrágicas en pacientes anticoagulados y recientemente se ha señalado como el segundo factor de riesgo de HEMR después de la anticoagulación al estar presente en el 58% de los casos en una serie de 115 pacientes 3 .…”
Section: Discussionunclassified